Review study of the First Stages for discovery and Producing Oil in Iraq - Qasim Hadi, Safaqis (Al-Adab Journal, 2019)
The Knowledge of oil in Iraq returns to thousands years, Indeed it was mentioned in the holy books and it was called (the eternal fire).The Babylonians may use it in the construction( buildings) as well as using t to align the walls . The ancient also used it in medicine and wars. Indeed , the population in Iraq as in Mendeli , Ghayara and Kirkuk used it by the old ways since the beginning of nineteenth Century. Thus the foreign companies came on often the other to search oil in Iraq after the other to search oil in Iraq after German delegation study for the geology of Iraq surface in 1871 .This company declared the existence of great quantity of oil in Iraq. Since that time , Iraq became the center of foreign companies competition for digging and producing oil. At that times many companies got privileges to invest oil especially Germany , British , Holland and U.S.A. The starting of the first world war effect on investing oil so that many companies would be established were ended by the beginning of oil nationalization in Iraq. The geographic distribution of oil wells differs for quantity and quality between the north and south places according to the quality of rocks and geological structure for Iraqi surface.